2021
DOI: 10.1177/0706743720984684
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Recreational Cannabis Legalization on the Prevalence of Cannabis Use Disorder and Psychotic Disorders: A Retrospective Observational Study

Abstract: Objectives: The principal objective of our study was to document the short-term impact of the legalization of recreational cannabis on active cannabis use, cannabis use disorder, and various psychotic disorders. Methods: We carried out a retrospective observational study of patients who were at least 12 years old and who had visited a psychiatrist in the emergency unit of the Centre hospitalier universitaire de Sherbrooke (CHUS). We included all the consultations of this type over a 5-month period, immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Our null results appear similar to those described in a recent medical-chart-review study comparing the prevalence of pre- versus post-legalization psychotic-disorder presentations ( n ≈ 741) occurring 2 years before and 5 months after legalization to two Sherbrooke, Québec psychiatric emergency department units, with the Sherbrooke-based study finding no evidence of any significant difference in the pre- versus post-legalization prevalence of a psychotic-disorder diagnosis in patients’ medical records. 30 As the authors noted, however, the comparison of the prevalence of pre- versus post-legalization psychotic-disorder presentations may have been confounded by treatment-service changes occurring during the study period via the initiation of new community-based psychiatric-treatment outreach programs [i.e., new availability of intensive psychiatric follow-ups services in the community; creation of a specialized first-episode (FEP) psychosis team], and such alterations may have differentially affected patterns of psychotic-disorder presentations to the psychiatric ED study sites across the pre- and post-legalization periods. 30 In relation to the current study, a number of factors may have contributed to the null results related to our target series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our null results appear similar to those described in a recent medical-chart-review study comparing the prevalence of pre- versus post-legalization psychotic-disorder presentations ( n ≈ 741) occurring 2 years before and 5 months after legalization to two Sherbrooke, Québec psychiatric emergency department units, with the Sherbrooke-based study finding no evidence of any significant difference in the pre- versus post-legalization prevalence of a psychotic-disorder diagnosis in patients’ medical records. 30 As the authors noted, however, the comparison of the prevalence of pre- versus post-legalization psychotic-disorder presentations may have been confounded by treatment-service changes occurring during the study period via the initiation of new community-based psychiatric-treatment outreach programs [i.e., new availability of intensive psychiatric follow-ups services in the community; creation of a specialized first-episode (FEP) psychosis team], and such alterations may have differentially affected patterns of psychotic-disorder presentations to the psychiatric ED study sites across the pre- and post-legalization periods. 30 In relation to the current study, a number of factors may have contributed to the null results related to our target series.…”
Section: Discussionmentioning
confidence: 99%
“… 30 As the authors noted, however, the comparison of the prevalence of pre- versus post-legalization psychotic-disorder presentations may have been confounded by treatment-service changes occurring during the study period via the initiation of new community-based psychiatric-treatment outreach programs [i.e., new availability of intensive psychiatric follow-ups services in the community; creation of a specialized first-episode (FEP) psychosis team], and such alterations may have differentially affected patterns of psychotic-disorder presentations to the psychiatric ED study sites across the pre- and post-legalization periods. 30 In relation to the current study, a number of factors may have contributed to the null results related to our target series. First, key indicators of patterns of cannabis use in Alberta and Ontario showed relatively little change after legalization.…”
Section: Discussionmentioning
confidence: 99%
“…It also found an increase in diagnoses of cannabis use disorder (17.7 to 24.3%; see source study for diagnostic standards) among adults but not underage patients. There were no differences in diagnoses of psychotic disorders (27.4 to 29.2%) but a greater proportion presented with a personality disorder (39.6 to 44.9%) after legalization (Vignault et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies examined changes in cannabis use disorder or harmful cannabis use (heavy cannabis use or cannabis use during pregnancy) following legalisation (Table 5) [8,25,34,35]. Studies examined multiple subgroups (pregnant women, general population, individuals seeking outpatient addiction services and individuals presenting at a psychiatric ED).…”
Section: Self-reported Cannabis Use Disorders or Harmful Cannabis Usementioning
confidence: 99%
“…Studies examined multiple subgroups (pregnant women, general population, individuals seeking outpatient addiction services and individuals presenting at a psychiatric ED). All studies used different measures of cannabis use with two studies using a validated tool for cannabis use disorders (Cannabis Use Disorders Identification Test-Revised, where a score of eight or greater constitutes problematic use and takes frequency of use, quantity used and severity of misuse into account and Severity of Dependence Scale, which assesses the psychological components of dependence, including anxieties about drug use) [8,34] and one study using a diagnosis of cannabis use disorder [35]. One study (n = 2615) found a significant increase in the prevalence of diagnosed cannabis use disorder in adults presenting to a psychiatric ED in Quebec 6 months following legalisation [35].…”
Section: Self-reported Cannabis Use Disorders or Harmful Cannabis Usementioning
confidence: 99%